The Application of Brand Resonance in Brand Building: A Systematic Literature Review - Xi, Jing; Hashim, Sharizal (International Review of Management and Marketing, 2026)
This systematic literature review examines brand resonance as a strategic tool for building strong consumer–brand relationships. Following PRISMA guidelines, extensive searches of Scopus and Web of Science yielded 992 publications, from which 446 peer-reviewed studies (2005–2025) were selected. Bibliometric analysis using CiteSpace identified 12 themes and revealed a paradigm shift from cognitive psychology to brand building after 2016. Findings indicate that brand resonance comprises four interconnected dimensions: behavioral loyalty, attitudinal attachment, sense of community, and active engagement. These elements collectively strengthen consumer loyalty and brand equity across diverse sectors including luxury products, hospitality, education, and halal markets. Emotional marketing, customer experiences, and social media marketing prove effective in cultivating brand resonance, with emotional approaches demonstrating greater potency than cognitive methods. The integration of attribution theory, brand experience theory, and the cognitive-affective-conative model provides a comprehensive theoretical framework explaining brand resonance mechanisms. This review contributes a conceptual framework linking antecedent factors—emotional value, brand experience, brand cognition, social interaction, perceived quality, and brand loyalty—to brand resonance and its behavioral outcomes, including repeat purchase intention and word-of-mouth advocacy. Research gaps regarding visual branding symbols in digital spaces are identified for future investigation.